Welcome to Religions, a New Open Access, Multidisciplinary and Comprehensive Online Journal - Kaufman, Peter Iver (Religions, 2010)
We always seem to be in the wake of some current event or controversy that reminds us just how important scholarly interest in religions has been, is, and will be. Fortunately, new sources for religious movements—even sources that illumine those movements’ origins—keep turning up, and many sources, long considered critical, are now accessible online. Furthermore, fresh developments in the disciplines that consistently make significant contributions to our understanding of religious personality, authority, devotion, and community—disciplines ranging from psychology, sociology, and anthropology to history, art history, philosophy, literary criticism, and political science—fuel general, as well as scholarly, interest in the world’s religions. Without exaggeration, one can claim we have an embarrassment of riches. Consequently, the study of religious crises, commitments, and critics of the latter has never been livelier. [...]